Sistem Pakar Mendiagnosa Penyakit Rabies Menggunakan Metode Certainty Factor - Resnawita Resnawita; Billy Hendrik (Lembaga Pengembangan Kinerja Dosen, 2023)
The increasingly rapid development of technology has changed the world, the launch of various new technologies has made people dependent on technology to do various jobs. An expert system is a system that is integrated with computer equipment in which there is knowledge, facts and reasoning techniques in solving problems that usually can only be solved by an expert in that field. For example, an expert system that analyzes rabies by relying on the symptoms a person feels. as a decision maker. Rabies is an acute infectious disease, attacks the central nervous system caused by Lyssavirus and will result in death, can attack all warm-blooded animals and humans. This disease is zoonotic, namely a disease that can be transmitted from animals to humans through the bite of a rabid animal. This system was designed with the aim of being a means of solving problems surrounding rabies using the factor certainty method. Factor certainty is a method for proving whether a fact is certain or uncertain in the form of metrics commonly used in expert systems. The percentage of confidence obtained by the expert system using the factor certainty method for diagnosing rabies reached 84% by referring to the data provided by the user to the expert system.